Investigating the use and knowledge of analgesics among IIUM Undergraduate Pharmacy students. - Mohd Zaini, Dayang Ummu Afifah; Roselan, Afiqah; Bohari, Nurul Syafiqah; Ahmad Nazri, Ain Nabihah; Mohd Fakhruddin, Ameerah; Mohd Taufek, Nor Hidayah (2019)
Introduction: Analgesics are commonly used to relieve pain and can be obtained through prescription or self-medication. Little is known regarding the use of analgesics among pharmacy students given their unique knowledge and training on medications. Objectives: The study aimed to investigate the use and knowledge of analgesics among IIUM Undergraduate Pharmacy Students in Kuantan, Pahang. Methods: A cross-sectional survey was conducted using a validated questionnaire among undergraduate pharmacy students from Year 1 to Year 4. The data from stratified sampling were analysed using IBM SPSS Statistics 22 for descriptive statistics. Results: A total of 371 students (82%) participated in the study (age range: 18-25 years). The analgesics used to treat fever (73.0%) and headache (69.3%) were paracetamol (96.5%), mefenamic acid (33.7%), ibuprofen (24.6%) and diclofenac sodium (20.5%). The average score for the knowledge was 5.4/9.0. The fourth year students had the highest knowledge score (6.7) compared to first (3.6), second (5.7) and third (6.1) year. Some took supplements to relieve pain (1.3%). The analgesics used from over the counter/pharmacist recommendation (56.1%) were chosen based on dosage form (52.6%), price (48%) and availability (63.1%). The sources of information were from lecturers (78.4%) and health care providers (73%). The sources of supply were community pharmacies (76.3%), government hospitals/clinics (44.5 %) and convenience stores (38.3%). Majority of them took analgesics with food (86.3%) whereas some experienced side effects (16.2%). Conclusion Analgesics were commonly used among pharmacy students through over the counter/pharmacist recommendation. The knowledge regarding analgesics needs to be improved among pharmacy students.